A PENROSE THAT CANNOT BE OPENED WITHOUT THREE HANDS LOCK AND ITS GEOMETRIC STRUCTURE (American Journal of Pedagogical and Educational Research, 2023)
The scientific article highlights the material about the types of locks and their device, about the positive impact of conducting geometric studies on the forms of the details of the lock to the development of technical creative abilities of a person.